2013
DOI: 10.1161/atvbaha.112.300234
|View full text |Cite
|
Sign up to set email alerts
|

Kalirin Promotes Neointimal Hyperplasia by Activating Rac in Smooth Muscle Cells

Abstract: Objective Kalirin is a multifunctional protein that contains two guanine nucleotide exchange factor (GEF) domains for the GTPases Rac1 and RhoA. Variants of KALRN have been associated with atherosclerosis in humans, but Kalirin’s activity has been characterized almost exclusively in the CNS. We therefore tested the hypothesis that Kalirin functions as a RhoGEF in arterial smooth muscle cells (SMCs). Methods and Results Kalirin-9 protein is expressed abundantly in aorta and bone marrow, as well as in cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 46 publications
(67 reference statements)
1
45
0
Order By: Relevance
“…The RhoGEF1 domain and RhoGEF2 domain activate Rac1 and RhoA, respectively. 17 Wu et al 16 demonstrated Kalirin-9 expression in the aorta, and that Kalirin expression was increased in a model of atherosclerosis, consistent with clinical findings. 18 They also established that Kalirin-9 is expressed by multiple cell types found within the vascular wall, including endothelial cells, VSMCs, and macrophages.…”
Section: See Accompanying Article On Page 702supporting
confidence: 53%
See 2 more Smart Citations
“…The RhoGEF1 domain and RhoGEF2 domain activate Rac1 and RhoA, respectively. 17 Wu et al 16 demonstrated Kalirin-9 expression in the aorta, and that Kalirin expression was increased in a model of atherosclerosis, consistent with clinical findings. 18 They also established that Kalirin-9 is expressed by multiple cell types found within the vascular wall, including endothelial cells, VSMCs, and macrophages.…”
Section: See Accompanying Article On Page 702supporting
confidence: 53%
“…The authors set out to test whether Kalirin-9 functions in VSMCs as a dual Rho-GEF in vitro and in vivo. 16 convincingly demonstrated that in VSMCs, despite the presence of a GEF domain specific for Rac1 and a GEF domain specific for RhoA, 17 Kalirin primarily mediates Rac1 activation via its RhoGEF1 domain, but does not alter RhoA activation, to promote VSMC migration.…”
Section: See Accompanying Article On Page 702mentioning
confidence: 97%
See 1 more Smart Citation
“…5H). Possible candidates include ArhGEF7 and Kalirin, since these exchange factors promote the proliferation and migration of vSMC in vitro and, in the case of Kalirin, neointima formation in vivo (44,45). Our results suggest that Vav3 also can represent a good candidate for this regulatory step (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Neointimal hyperplasia, induced by carotid endothelial denudation, was significantly reduced in VSMC-specific Kalrn -/1 mice compared with control mice. Reduced Kalrn function gave normal RhoA activation but diminished Rac1 activation in serum-, endothelin-1-, or PDGF-stimulated VSMC, as assessed by reduced Rac1-GTP levels, PAK1 activation, and reduced VSMC proliferation and migration (Wu et al, 2013a). These data suggest that the Rac-GEF domain is dominant over the Rho-GEF domain in Kalrn under these conditions.…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 77%